Tinjauan Hukum Islam Terhadap Praktik Mediasi Dalam Penyelesaian Perkara Cerai Gugat Di Pengadilan Agama Wates Yogyakarta - M Nurul Fadhlan; Dzulkifli Hadi Imawan (MASADIR: Jurnal Hukum Islam, 2022)
Court is an institution that plays a role in resolving cases through mediation, while in Islam it is called sulh and mediation is an effort to reconcile the parties to resolve the problems they face, as a mediator must be neutral and impartial to anyone because the mediator acts as a mediator for them, the mediator also offers a solution or a way out for them. The purpose of this thesis is to find out how the practice of mediation in the settlement of divorce cases at the Wates Religious Court and also to find out the factors that cause successful and unsuccessful mediation in the process of resolving divorce cases. This research uses field research and is supported by library research This research approach is a qualitative research using descriptive data analysis technique. And the source of the data found in the form of primary and secondary data. The data collection techniques used in this study used interviews and literature studies. The findings obtained by researchers in this case are as follows: first, the implementation of the mediation process at the Wates Religious Court has not been fully effective, this is proven by data from the last 2 years of divorce cases. sued only ten couples who succeeded in mediation. The second, from the results of interviews with the mediator judge, explained that there were also several factors that caused the mediation process to be unsuccessful, namely from his side there was also no goodwill to be together and there was no transparency regarding the parties' household problems. And the factors for the success of the mediation are because the parties find common ground from their problems, and the parties have agreed to make peace and the support factor from the family.